O conceito de "fire smart territory": contributo para a mudança de perspetiva na gestão dos incêndios florestais em Portugal - Tedim, Fantina (2016)
The symptomatic approach to fire management focused on "fire control" through the suppression of all fires did not solve or control the problem of wildfires which has a structural root. The resolution of the problem can only be found in the Coupled Human and Natural System where it is originated and developed. In this paper the concept of "Fire Smart Territory" is introduced. It is based on a new perspective on the management of wildfires that promotes a better balance and interrelationship between prevention and suppression.